PENGEMBANGAN METODE PENDUGAAN KEDALAMAN PERAIRAN DANGKAL MENGGUNAKAN DATA SATELIT SPOT-4. STUDI KASUS: TELUK RATAI, KABUPATEN PESAWARAN - Arief, Muchlisin; Hastuti, Maryani; Asriningrum, Wikanti; Parwati, Ety; Budiman, Syarif; Prayogo, Teguh (Institut Teknologi Sepuluh Nopember, 2013)
Bathymetric estimation of shallow water depth using satellite remote sensing data becomes more prevalent. However, when these methods are implemented for areas with different environments, the results indicate the presence of irregularities. To minimize the deviation, conducted the merger of the information obtained from field measurements with reflectance values SPOT-4 satellite imagery. This paper proposed the method development for bathymetric estimation of shallow water depth based on the correlation function between the depth value of direct measurements using a